The Cynomolgus Macaque Natural History Model of Pneumonic Tularemia for Predicting Clinical Efficacy Under the Animal Rule - Guina, Tina; Lanning, Lynda L.; Omland, Kristian S.; Williams, Mark S.; Wolfraim, Larry A.; Heyse, Stephen P.; Houchens, Christopher R.; Sanz, Patrick; Hewitt, Judith A. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is a highly infectious Gram-negative bacterium that is the etiologic agent of tularemia in animals and humans and a Tier 1 select agent. The natural incidence of pneumonic tularemia worldwide is very low; therefore, it is not feasible to conduct clinical efficacy testing of tularemia medical countermeasures in human populations. Development and licensure of tularemia therapeutics and vaccines need to occur under the Food and Drug Administration’s (FDA’s) Animal Rule under which efficacy studies are conducted in well-characterized animal models that reflect the pathophysiology of human disease. The Tularemia Animal Model Qualification Working Group is seeking qualification of the cynomolgus macaque (Macaca fascicularis) model of pneumonic tularemia under Drug Development Tools Qualification Programs with the FDA based upon the results of studies described in this manuscript. Meta-analyses of data on survival, average time to death, average time to fever onset, average interval between fever and death, and bacteremia; together with summaries of clinical signs, necropsy findings and histopathology from the animals exposed to aerosolized F. tularensis Schu S4 in five natural history studies and one antibiotic efficacy study form the basis for the proposed cynomolgus macaque model. Results support the conclusion that signs of pneumonic tularemia in cynomolgus macaques exposed to 300 to 3,000 colony forming units (cfu) aerosolized F. tularensis Schu S4, under the conditions described herein, and human pneumonic tularemia cases are highly similar. Animal age, weight and sex of animals challenged with 300 to 3,000 cfu Schu S4 did not impact fever onset in studies described herein. This study summarizes critical parameters and endpoints of a well-characterized cynomolgus macaque model of pneumonic tularemia and demonstrates this model is appropriate for qualification, and for testing of tularemia therapeutics under Animal Rule.